REGISTER OF TRANSNATIONAL TERRORIST GROUP: FORM, MEANING, PURPOSE, AND FUNCTIONS - Zahra, Tsurayya Yusra Zahirah (Universitas Ahmad Dahlan, 2022)
The register is a language variation that can become the identity of a community group. The register is also a marker of an individual a member of a particular community group. One of them is the register used by terrorist groups. Indonesia has detected two streams of transnational terrorist groups in this country, namely ISIS and Al-Qaeda. The Sociolinguistics studies specification in the uses of registers by the two terrorism groups investigated using a qualitative descriptive method. This research takes the main sources from the electronic news platform and channel belonging to one of the suspected terrorist groups. The results showed that there were differences in the form of language selection in the use of registers in each group. In addition, the analysis of the use of terrorist registers from the two groups also clearly shows the intent and purpose of using the registers. Through this research, researcher hoping that the community can increase awareness and sensitivity to all social processes around them, especially in the process of speech acts in the community, by not ignoring linguistic signs that they do not know.